Application of polymerized porcine hemoglobin in the ex vivo normothermic machine perfusion of rat livers - Li, Bin; Zhang, Jie; Shen, Chuanyan; Zong, Tingting; Zhao, Cong; Zhao, Yumin; Lu, Yunhua; Sun, Siyue; Zhu, Hongli (Frontiers in Bioengineering and Biotechnology, 2022)
Background: In contrast to traditional static cold preservation of donor livers, normothermic machine perfusion may reduce preservation injury, improve graft viability and potentially allows ex vivo assessment of graft viability before transplantation. The polymerized porcine hemoglobin is a kind of hemoglobin oxygen carrier prepared by crosslinking porcine hemoglobin by glutaraldehyde to form a polymer. The pPolyHb has been proved to have the ability of transporting oxygen which could repair the organ ischemia-reperfusion injury in rats. Objective: In order to evaluate the effectiveness of rat liver perfusion in vitro based on pPolyHb, we established the NMP system, optimized the perfusate basic formula and explored the optimal proportion of pPolyHb and basal perfusate. Methods: The liver was removed and perfused for 6 hours at 37 °C. We compared the efficacy of liver perfusion with different ratios of pPolyHb. Subsequently, compared the perfusion effect using Krebs Henseleit solution and pPolyHb perfusate of the optimal proportion, and compared with the liver preserved with UW solution. At 0 h, 1 h, 3 h and 6 h after perfusion, appropriate samples were collected for blood gas analysis and liver injury indexes detection. Some tissue samples were collected for H&E staining and TUNEL staining to observe the morphology and detect the apoptosis rate of liver cells. And we used Western Blot test to detect the expression of Bcl-2 and Bax in the tissues. Results: According to the final results, the optimal addition ratio of pPolyHb was 24%. By comparing the values of Bcl-2 / Bax, the apoptosis rate of pPolyHb group was significantly reduced. Under this ratio, the results of H&E staining and TUNEL staining showed that the liver morphology was well preserved without additional signs of hepatocyte ischemia, biliary tract injury, or hepatic sinusoid injury, and hepatocyte apoptosis was relatively mild. Conclusion: Through the above-mentioned study we show that within 6 hours of perfusion based on pPolyHb, liver physiological and biochemical activities may essentially be maintained in vitro. This study demonstrates that a pPolyHb-based perfusate is feasible for NMP of rat livers. This opens up a prospect for further research on NMP.